Impact of Alcohol Outlet Density on Reported Cases of Child Maltreatment in Japan: Fixed Effects Analysis - Koyama, Yuna; Fujiwara, Takeo (Frontiers in Public Health, 2019)
Background Parental drinking habits or binge drinking are a known risk factor of child maltreatment. Though drinking habits are affected by alcohol outlet density, the direct association between alcohol outlet density and child maltreatment is still controversial. Purpose This study aimed to examine the impact of off-premises alcohol outlet density on child maltreatment cases reported to Child Guidance Centers in Japan. Methods A fixed-effect model was used to investigate the association between a change in off-premises alcohol outlet density and a change in child maltreatment cases in each unit. Time-series of cross-sectional ecological data collected from across Japan over 16 years (2000 to 2015) was used, and maltreatment cases were further sub-grouped by type of maltreatment (physical, sexual, psychological abuse and neglect) and by perpetrators (father, stepfather, mother and stepmother). Results The association between alcohol outlet density and total cases of child maltreatment was not observed (coefficient = 0.98, 95% confidence interval: -6.30, 8.25). However, alcohol outlet density was shown to be positively associated with neglect (coefficient = 3.08, 95% confidence interval: 0.54, 5.62), which indicates that 1 alcohol outlet per 1,000 adults increase would lead to 3 more neglect cases per 10,000 children. Also, a negative association was observed between a change in the incidence of total child maltreatment by father and a change in alcohol outlet density (coefficient = -3.03, 95% confidence interval: -5.78, -0.28). Conclusion The findings suggest that drinking habits may have a causal effect on the increasing cases of neglect and decrease in maltreatment by father in Japan.